The midpoint between the two points are (0,1/2)
Answer:
The correct answer is x = 3 and y = 2.
Step-by-step explanation:
There are many ways to solve systems of equations like this, but I'm going to use substitution. This means taking the value of y given by the second equation and plugging it into the first equation. This is modeled below:
2x - y = 4
2x - (-2x+8) = 4
Now, we can simplify the left side of the equation.
2x + 2x - 8 = 4
4x - 8 = 4
We should add 8 to both sides as the next step.
4x = 12
Now we can divide by 4.
x = 3
To solve for y, we can substitute this value found for x back into either one of our original equations.
y = -2x + 8
y = (-2*3) + 8
y = -6 + 8
y = 2
Therefore, the correct answer is x = 3 and y = 2.
Hope this helps!
Answer:
13
Step-by-step explanation: 325/25=13
Answer:
y = 3x² - 6x - 72
Step-by-step explanation:
Since the roots are x = - 4 and x = 6 then the factors are
(x + 4) and (x - 6) and the quadratic function is
y = a(x + 4)(x - 6) ← a is a multiplier, in this case 3, so
y = 3(x + 4)(x - 6) ← expand factors and distribute by 3
y = 3(x² - 2x - 24)
y = 3x² - 6x - 72